KETERAMPILAN RECEPTIONIST PADA HOTEL NOVOTEL KOTA PEKANBARU - Chintya Putri Wardani; Teguh Widodo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Along with the times, many Hotels in Indonesia are popping up to improve their skills, one of them in Pekanbaru city is the Novotel Hotel which is an international standard Hotel. The Novotel Hotel Pekanbaru is still considered lacking in the skills of its employees due to complaints from guest regarding it Receptionist skills. Therefore, the authors are interested in bringing up thr study entitled Receptionist skills at the Novotel Hotel Pekanbaru city. This study aims to determine how the response of guests staying at the Novotel Hotel Pekanbaru to Receptionist skills at the Novotel Hotel. This research was conducted at the Novotel Hotel on Jalan Riau No. 59 Pekanbaru. This research was carried out for 6 months, starting from September 2019 until March 202. This research uses quantitative descriptive methods. Data collection techniques using observation, documentation and questionnaires. The sampling technique was determined using accidental sampling technique. The sample of this study was guest staying at the Novotel Hotel Pekanbaru. The result of this study indicate that overall the respondents gave a good response to the Receptionist skill at the Novotel Hotel Pekanbaru city, this is evidenced by the result of the score of the guest responses that stayed with good grades, in additional Receptionist is an employee who will give first and last impressions as well direct contact with guest. Keywords: Skills, Receptionist and Hotel.